PENGARUH UKURAN KOMITE AUDIT, SOLVABILITAS, DAN OPINI AUDIT TERHADAP AUDIT REPORT LAG (Studi kasus pada perusahaan property dan real estate dan energy yang listing di Bursa Efek Indonesia pada tahun 2018 - 2020) - Fariz Najmi Arhamullah, (2022)
This study aims to analyze how the influence of Audit Committee Size, Solvency, and Audit Opinion on Audit Report Lag. By using purposive sampling as a sample collection technique, 324 sample data were generated from 108 property & real estate and energy sector companies listed on the Indonesia Stock Exchange during the 2018-2020 period. Multiple linear regression analysis is a data analysis technique used with panel data regression using STATA 16 software and a significance level of 5%. The results show that the size of the audit committee has no effect on audit report lag. However, the results of solvency have a positive effect on audit report lag and audit opinion has a negative effect on audit report lag. The ability of the independent variable used in this study is able to explain the audit report lag variable of 11.65%, so that the other 88.35% is influenced by other factors.